Optimized deposition parameters for titanium nitride coatings: Enhancing mechanical properties of Al 6011 substrates via DC sputtering - Margono, Margono; Darmadi, Djarot Bangun; Gapsari, Femiana; Widodo, Teguh Dwi; Kozin, Muhammad; Puranto, Prabowo; Kamil, Muhammad Prisla; Fitriani, Diah Ayu; Azahra, Siti Amalina; Andriyanti, Wiwien (Universitas Muhammadiyah Magelang, 2024)
The growing demand for advanced coatings in industries such as aerospace and automotive necessitates materials with superior hardness, wear resistance, and thermal stability. Despite advancements in ternary coatings, research on binary Titanium Nitride (TiN) coatings remains limited, particularly in optimizing deposition parameters for lightweight aluminum substrates. This study aims to investigate the effects of sputtering parameters, specifically Ar:N₂ gas ratios and deposition durations, on the mechanical properties of TiN coatings on Al 6011 substrates. The optimized conditions (70Ar:30N₂ gas ratio and 60-minute deposition) yielded a 165% increase in surface hardness (88.92 HV) and a 54% reduction in wear rate compared to untreated samples. XRD and SEM analyses confirmed the dense microstructure and strong (200) phase orientation contributing to these enhancements. This research highlights a cost-effective and scalable approach to improving the performance of aluminum alloys, bridging the gap between fundamental studies and industrial applications.